District characteristics: Household economic status of families diagnosed with tuberculosis in Indonesia - Ema Novita Deniati; Pandu Riono; Muhammad Noor Farid (AOSIS, 2022)
The 2016 Global TB Report stated that only 35.3% of people with TB were reported in Indonesia from around 1,020,000 estimated incidents. This of course makes the risk of people with TB who have not been found to transmit the disease will increase. Of all districts in Indonesia, not all of them have good TB case finding coverage rates. Many factors lead to this, resulting in inequality in the discovery and reporting of TB cases. It is important to know the characteristics of districts with households diagnosed with TB. The research using secondary data analysis using Riskesdas 2013 data and 2014 Podes data studied the characteristics of districts with households diagnosed with TB in Indonesia. The results showed that there was an influence of district characteristics with the proportion of low economic households (0.6%) on the characteristics of districts with households diagnosed with TB. This study suggests strengthening programs related to TB prevention and control efforts in at-risk households and as a basis for sharpening intervention priorities based on the level of TB epidemics in districts/cities.